Ultrafiltration rate adjusted to body weight and mortality in hemodialysis patients - Raul Fernandez-Prado (Elsevier, 2021)
Background and aims: Mortality among hemodialysis patients remains high. An elevated ultrafiltration rate adjusted by weight (UFR/W) has been associated with hypotension and higher risk of death and/or cardiovascular events. Methods: We evaluated the association between UFR/W and mortality in 215 hemodialysis patients. The mean follow-up was 28 ± 6.12 months. We collected patients’ baseline characteristics and mean UFR/W throughout the follow-up. Results: Mean UFR/W was 9.0 ± 2,4 and tertiles 7.1 y 10.1 mL/kg/h. We divided our population according to the percentage of sessions with UFR/W above the limits described in the literature associated with increased mortality (10.0 ml/kg/h and 13.0 mL/kg/h). Patients with higher UFR/W were younger, with higher interdialytic weight gain and weight reduction percentage but lower dry, pre and post dialysis weight. Throughout the follow-up, 46 (21.4%) patients died, the majority over 70 years old, diabetic or with cardiovascular disease. There were neither differences regarding mortality between groups nor differences in UFR/W among patients who died and those who did not. Contrary to previous studies, we did not find an association between UFR/W and mortality, maybe due to a higher prevalence in the use of cardiovascular protection drugs and lower UFR/W. Conclusions: The highest UFR/W were observed in younger patients with lower weight and were not associated with an increased mortality. Resumen: Antecedentes y objetivo: La mortalidad de los pacientes en hemodiálisis es alta. Una tasa de ultrafiltración horaria ajustada por peso (UFR/W) elevada se ha asociado a episodios de hipotensión arterial y mayor riesgo de muerte y/o eventos cardiovasculares. Material y métodos: Hemos evaluado la asociación entre UFR/W y mortalidad en 215 pacientes en hemodiálisis prevalentes seguidos durante 28 ± 6,12 meses. Se estimaron características clínicas basales y UFR/W media a lo largo del seguimiento. Resultados: La UFR/W media fue 9,0 ± 2,4 y los terciles 7,1 y 10,1 mL/kg/h. Se categorizó a la población en función del tiempo que habían estado con UFR/W igual o superior a los puntos de corte descritos en la literatura como asociados a mayor mortalidad (10,0 mL/kg/h y 13,0 mL/kg/h). Los pacientes con mayor UFR/W fueron más jóvenes, con mayor ganancia de peso interdiálisis y porcentaje de reducción de peso, pero con menor peso seco, inicial y final. Durante el seguimiento, fallecieron 46 (21,4%) pacientes de los cuales la mayoría eran >70 años, diabéticos o con enfermedad cardiovascular. No hubo diferencias en mortalidad entre los grupos de UFR/W ni diferencias en la UFR/W entre los fallecidos y no fallecidos. En comparación con estudios previos donde describieron la asociación entre UFR/W y mortalidad, en nuestra población había más prevalencia de medicación protectora cardiovascular y no se observaron UFR/W tan altas. Conclusión: En nuestro medio, la UFR/W más elevada se observó en pacientes más jóvenes y de menor peso y no se asoció a mayor mortalidad.